The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1982
DOI: 10.1113/jphysiol.1982.sp014022
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis of acetylcholine in skeletal muscles of the rat

Abstract: 1. The synthesis of acetylcholine (ACh) has been measured in homogenates of the sciatic nerve, normal and denervated extensor digitorum longus (e.d.l.) muscles, and central (innervated) and peripheral (non-innervated) parts of the diaphragm of the rat. The synthesis proceeded under conditions accepted as optimal for the activity of choline acetyltransferase (ChAT). In view of the finding that cardiac carnitine acetyltransferase (CarAT) is able to acetylate choline (White & Wu, 1973), the possible contribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
93
1

Year Published

1985
1985
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(95 citation statements)
references
References 30 publications
1
93
1
Order By: Relevance
“…However, there are several reports documenting the ability of muscle cells to synthesize ACh, either via ChAT or via the enzyme carnitine acetyltransferase. ACh-synthesizing activity and/or ACh release have been demonstrated in myoblasts (Krause et al 1995;Fu et al 1998), skeletal muscle fiber (Tucek 1982;Miledi et al 1982), and smooth muscle fibers of the human skin . Moreover, airway smooth muscle cells have been shown to display ChAT immunoreactivity .…”
Section: Discussionmentioning
confidence: 99%
“…However, there are several reports documenting the ability of muscle cells to synthesize ACh, either via ChAT or via the enzyme carnitine acetyltransferase. ACh-synthesizing activity and/or ACh release have been demonstrated in myoblasts (Krause et al 1995;Fu et al 1998), skeletal muscle fiber (Tucek 1982;Miledi et al 1982), and smooth muscle fibers of the human skin . Moreover, airway smooth muscle cells have been shown to display ChAT immunoreactivity .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that carnitine acetyltransferase (CarAT) also acetylates choline (White and Wu, 1973;Rossier, 1977;Tucek, 1982). The syn thesis of ACh by CarAT as well as by ChAT has been shown in cardiac (White and Wu, 1973) and skeletal (Tucek, 1982) muscle. It was estimated that about one-half of the ACh synthesized from choline in innervated skeletal muscle was catalyzed by CarAT (Tucek, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…The syn thesis of ACh by CarAT as well as by ChAT has been shown in cardiac (White and Wu, 1973) and skeletal (Tucek, 1982) muscle. It was estimated that about one-half of the ACh synthesized from choline in innervated skeletal muscle was catalyzed by CarAT (Tucek, 1982). Although it is not known whether vascular smooth muscles also contain CarAT, a small but significant amount of acetylated products that are not synthesized by ChAT has been demonstrated in denervated ear arteries of the rabbit (Florence et aI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The content of ACh in tissues with cholinergic innervation is very stable. If the release of ACh is augmented as a consequence of increased functional activity of mammalian cholinergic neurons, the ACh is replaced almost immediately by new synthesis (MacIntosh & Collier 1976, Tucek 1982. However, the resynthesis is slower in piscine electric organ (Dunant et al 1974(Dunant et al , 1977.…”
Section: Discussionmentioning
confidence: 99%